Declarative Agent Languages and Technologies VII 7th International Workshop, DALT 2009, Budapest, Hungary, May 11, 2009. Revised Selected and Invited Papers - Baldoni, Matteo; Bentahar, Jamal; van Riemsdijk, M. Birna; Lloyd, John (Lecture Notes in Artificial Intelligence, 2010)
This book constitutes the thoroughly refereed post-workshop proceedings of the 7th International Workshop on Declarative Agent Languages and Technologies, DALT 2009, held in Budapest, Hungary, on May 11, 2009, as a satellite workshop of the 8th International Joint Conference on Autonomous Agents and Multiagent Systems, AAMAS 2009. The 11 revised full papers presented together with 1 invited lecture and 3 invited papers from the AAMAS main conference - substantially enhanced after the workshop - were carefully selected from 17 initial submissions. The papers combine declarative and formal approaches with engineering and technology aspects of agents and multiagent systems and focus especially on areas such as the semantic web, service-oriented computing, web services, security, and electronic contracting.